Perancangan Sistem Informasi Monitoring Berbasis Web Untuk Admin Kantor Pada PT. Gemilang Sejahtera Abadi Kutai Timur - Reza Abi Mubaroq; Akhmad Baihaqi; Purbawati Purbawati; Mad Yusup; Ida Rosanti (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
PT. Gemilang Sejahtera Abadi (GSA) is a company engaged in the oil palm plantation business, which is spread across the East Kutai Regency, precisely in Long Mesangat District. It is still difficult for office admins to monitor plantation results and production results by relying on paper records, via telephone and SMS, making it difficult to understand palm oil production data. The computerized system used when the research was conducted still used Microsoft Excel and Microsoft Word. The purpose of this study was to create a web-based Monitoring Information System Design application for the PT. Gemilang Sejahtera Abadi office admin. The method used is the Waterfall method which consists of 5 stages, namely: communication, planning, modeling, construction and system submission. The system created is web-based using the PHP programming language and MySQL database.The results of the study concluded that the design of the plantation production monitoring system for the office admin can be implemented and is expected to help the office admin in managing harvest data and can reduce errors in the data input process.